Investigando el estilo personal del terapeuta: Correspondencia entre las autodescripciones y la observación de jueces externos - Fernández-Alvarez, Javier; Castañeiras, Claudia; García, Fernando; Gómez, Beatriz; Fernández-Alvarez, Héctor (Revista de Psicopatología y Psicología Clínica, 2017)
Abstract: Correspondence between self-descriptions and observations of external judges: A study on the personal style of the therapist. The personal style of the therapist (PST) is defined as the set of characteristics that lead the therapist to behave in a particular professional way. This empirical study aims to provide evidence of the concurrent validity of the EPT-C, an instrument to assess PST. Cluster analysis was performed with data from 79 audio-taped recorded sessions of 20 psychotherapists. The contrasting groups’ method was applied to compare EPT-C scores with the scores of the Guide for the Observation of the Therapist Aiglé (GOTA-v) as the criterion variable. The mean values, obtained in the EPT-C dimensions of three therapists’ clusters arising from the sessions’ observations and codification of emerging categories, were compared. Significant differences were found in two EPT-C dimensions: attentional and operative. These results are evidence of the concurrent validity of the EPT-C questionnaire. Resumen: El estilo personal del terapeuta (EPT) se conceptualiza como el conjunto de condiciones singulares que conducen a un terapeuta a operar en su desempeño profesional. El objetivo de este estudio empírico es aportar evidencia sobre la validez concurrente de un instrumento que evalúa el EPT (EPT-C). Se realizó un análisis de cluster a partir de 79 sesiones transcriptas de 20 psicoterapeutas. Para ello, se aplicó metodología de grupos contrastados para comparar los puntajes del EPT-C con los valores de la Guía de Observación del Terapeuta Aiglé (GOTA-v) como variable criterio. Se compararon las medias obtenidas en las dimensiones EPT-C para tres clusters de terapeutas, identificados a partir de la observación de las sesiones y la codificación de las categorías emergentes. Se obtuvieron diferencias significativas en dos dimensiones del el EPT-C: la atencional y la operativa. Los resultados evidencian la validez concurrente del instrumento EPT-C para evaluar el EPT.